AGRONOMIC COMPARISON OF THREE SOYBEAN VARIETIES (GLYCINE MAX) SUBJECTED TO ORGANIC TREATMENT WITH COW DUNG IN BUHIMBA (NORTH KIVU, DR CONGO) - Rusangiza Samuel Roland; Basimine Lulemire Bienfait (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2025)
Three improved varieties of soya (glycine max) subjected to an organic treatment based on cow dung were studied in buhimba in north kivu. The experimental design adopted was that of completely randomised blocks (crb) with 3 replications. The aim was to assess the yields of three soya varieties under the ecological conditions of buhimba. After applying 10t/ha of cow dung on the experimental site, the yields obtained were 7.727 t/ha ± 2.866 for the canada variety, 8.7 t/ha ± 2.107 for the sb24 variety and 6.983 t/ha ± 1.675 for the imperial variety considered as a control. After statistical analysis using a single-factor anova, comparison of the means at the 5% threshold revealed that there was no difference between the above yield averages. On the one hand, the soil in the study area, consisting of andosols, would be influenced by the application of cow dung, which would in turn have a positive effect on improving ph. Furthermore, the genetic make-up of these three varieties would have had some influence on their respective yields under similar conditions